Innovation capacity, food system development, and the size of the agricultural research system - Nin-Pratt, Alejandro; Stads, Gert-Jan (Frontiers in Sustainable Food Systems, 2023)
This article contributes to a better understanding of the context in which agricultural R&D investment takes place in low- and middle-income countries, and how innovation capacity, the development of the food system, and the size of the research system affect R&D investment. The results reveal that there is a high and positive correlation between innovation capacity and the development of the food system and a negative correlation between these two indicators and the size of the agricultural research system in low¬- and middle-income countries. The lower overall quality and level of development of the education and scientific research systems in countries with small agricultural research systems are important factors contributing to reduced innovation capacity. In addition, countries with small agricultural research systems are challenged with a comparatively poor innovation environment, poor market development, a weak private sector, a lack of competition in domestic markets, and a largely rural population with poor links to markets. The results of the analysis stress the need to increase the efficiency and productivity of agricultural research by implementing policies that get the most out of available resources while minimizing the negative effect of small-scale research operations. Increased coordination and integration of agricultural research at the regional and global level can help avoid duplication, enhance the efficiency of small-scale organizations, and make research more cost-effective and impactful.